Utilizing educational data mining techniques for improved learning emerging research and opportunities - Bhatt, Chintan M. 1988-; Srinivas Sajja, Priti; Liyanage, Sidath (IGI Global, 2019)
A critical scholarly resource that explores data mining and management techniques that promote the improvement and optimization of educational data systems. The book intends to provide new models, platforms, tools, and protocols in data science for educational data analysis and introduces innovative hybrid system models dedicated to data science. Including topics such as automatic assessment, educational analytics, and machine learning, this book is essential for IT specialists, data analysts, computer engineers, education professionals, administrators, policymakers, researchers, academicians, and technology experts